1989
DOI: 10.1164/ajrccm/140.4.1012
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Pneumonia by Auscultation of the Lungs in the Lateral Decubitus Positions

Abstract: Forty-five acutely ill, coughing patients, three with acute dyspnea and cardiomegaly, and 37 control subjects were placed in lateral decubitus positions for auscultation of their dependent lungs to determine if this maneuver would elicit inspiratory crackles, signs of pneumonia. In the upright position, auscultation of the lungs was normal in all control subjects and in lateral decubitus positions their dependent lungs revealed transient late inspiratory crackles in seven of the 37 (18.9%), and transient inspi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…A previously published study of rales in the LDP also found this finding useful in the detection of pneumonia. 10 In our study, direct percussion was of limited value in detecting pneumonia, and values were variable. Although auscultatory percussion had high specificity, values were low or unmeasurable.…”
Section: Commentmentioning
confidence: 60%
“…A previously published study of rales in the LDP also found this finding useful in the detection of pneumonia. 10 In our study, direct percussion was of limited value in detecting pneumonia, and values were variable. Although auscultatory percussion had high specificity, values were low or unmeasurable.…”
Section: Commentmentioning
confidence: 60%
“…Unfortunately findings obtained with a stethoscope are rather subjective [6,14]. It has been suggested, that an objective method such äs Computer based lung sound analysis could improve the Situation.…”
Section: Introductionmentioning
confidence: 99%
“…In einer Studie über Auskultationsbefunde bei Pneu monien fanden die Untersucher bei 19 % der gesunden Kontrollen in seitlich liegender Posi tion spätinspiratorische Rasselgeräusche in der unten liegenden Lunge. Diese Nebengeräusche verschwanden aber nach ein bis zwei tiefen Atemzügen [22]. …”
unclassified